Cận dưới độ phức tạp Otomat hữu hạn đoán nhận siêu ngôn ngữ chính quy - Ruận, Đặng Huy; Ổn, Phùng Văn (Journal of Computer Science and Cybernetics, 2016)
Some results of regular hyper-language [1] and the complexity of finite automaton recognizing regular hyper-language [2] are considered. In this paper we consider the lower limits of the complexity of finite automaton recognizing regular hyper-language.